Enhancing Competitiveness Business Strategy of Organic Vegetables Using Analytical Hierarchy Process (AHP) - Pristiana Widyastuti (DeReMa (Development Research of Management): Jurnal Manajemen, 2017)
Public awareness about healthy lifestyles leads people to want to understand more about the food they consume. Choosing organic vegetables is one alternative choices when seeking to have a healthy body and healthy lifestyle. Unfortunately, not a lot of organic vegetable farmers in Indonesia succeed in seizing the organic vegetable market rather than the non-organic and the competition with imported organic vegetables into Indonesia prevents farmers from thriving. This study aims to: 1) Analyze the factors affecting the competitiveness of the organic vegetables market; 2) Analyze the appropriate strategy for increasing the competitiveness of the organic vegetables market; 3) Analyze the factors priority strategies for improving the competitiveness of the organic vegetables market. Porter's Generic Model and Analysis Analytical Hierarchy Process (AHP) is used to determine the best strategy. The research found that organic vegetables marketing channels are still dominated by conventional market; the higher cost for intensive cultivation of organic vegetables. The main strategies are derived from the analysis is focusing on market delivery. There needs to be retailers of organic vegetables either modern or traditional to display these products. The establishment of organic vegetable outlets and online marketing that are not dependent on large retail (hypermarket) become recommendations in this study.